PENINGKATAN KEMAMPUAN GURU SEKOLAH DASAR DALAM MENGGUNAKAN MEDIA PEMBELAJARAN MELALUI KELOMPOK KERJA GURU DIDAERAH BINAAN III KECAMATAN GROGOL - Minarti Minarti (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2010)
The aims of this research are: to improve the ability of teachers in elementary school utility the study media through team teacher of working area guide III district Grogol school year 2009/2010,The research was conducted at state elementary school of area guide III district Grogol school year 2009/2010 The research was an action research. The research of action this entangle 7 elementary school. The teacher of class VI as sampel and headmaster assist in monitoring, The subjects of research were headmaster at that elementary school, the teacher of class VI as sampel and headmaster assist in monitoring. The collect of data were obtained by indepth interviewing, observation, discussion with the subjects of the research, the study of documents, and test. Meanwhile, data analysis using critical analysis technique and comparative-descriptive technique. The research was conducted in three cycles and the objectives of research was obtained successfully. The results of this action research were: to improve the ability of teachers utility the study media through team teacher of working in elementary school teacher area III district Grogol Sukoharjo, namely equal to 12,71%. Key Word: Ability of teacher, Team Teacher of Working, Utility of Media